Pengaruh Profitabilitas, Leverage, dan Likuiditas Terhadap Nilai Perusahaan dengan Ukuran Perusahaan sebagai Variabel Moderasi (studi pada sector industry barang consumer primer tahun 2019-2021) - Athiy Dina Rosihana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to analyze whether profitability, leverage and liquidity have an influence on firm value with firm size as a moderating variable. The population of this study are companies in the Primary Consumer Goods Industry sector which are listed on the Indonesia Stock Exchange in 2019-2021. Using purposive sampling technique, 25 companies were taken as research samples. The research method is quantitative using the SPSS 25.0 program. Data analysis used descriptive statistical analysis methods, classic assumption test, multiple linear regression analysis, definite T-test, and moderate regression analysis (MRA). The results of the study found that only profitability (ROE) had a significant effect on firm value (PBV), while leverage (DER) and liquidity (CR) had no significant effect on firm value. Firm size cannot moderate the relationship between Profitability (ROE), Leverage (DER) and liquidity (CR) with firm value.